2020
DOI: 10.18632/aging.103655
|View full text |Cite
|
Sign up to set email alerts
|

Activation of C-reactive protein proinflammatory phenotype in the blood retinal barrier in vitro: implications for age-related macular degeneration

Abstract: The retinal pigment epithelium (RPE) is considered one of the main targets of age-related macular degeneration (AMD), the leading cause of irreversible vision loss among the ageing population worldwide. Persistent low grade inflammation and oxidative stress eventually lead to RPE dysfunction and disruption of the outer bloodretinal barrier (oBRB). Increased levels of circulating pentameric C-reactive protein (pCRP) are associated with higher risk of AMD. The monomeric form (mCRP) has been detected in drusen, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Moreover, mononuclear cell migration increased when exposed to conditioned medium from mCRP-treated RPE cells, but not in pCRP-or control-treated conditioned media [78]. Interestingly, topological localization of mCRP determines the RPE pro-inflammatory response as RPE disruption is only observed when mCRP is exposed to the apical domain [77]. These findings together with the fact that there is no transcription of CRP in the retinal tissue, led us to study how CRP isoforms could accumulate in the subretinal space.…”
Section: C-reactive Proteinmentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, mononuclear cell migration increased when exposed to conditioned medium from mCRP-treated RPE cells, but not in pCRP-or control-treated conditioned media [78]. Interestingly, topological localization of mCRP determines the RPE pro-inflammatory response as RPE disruption is only observed when mCRP is exposed to the apical domain [77]. These findings together with the fact that there is no transcription of CRP in the retinal tissue, led us to study how CRP isoforms could accumulate in the subretinal space.…”
Section: C-reactive Proteinmentioning
confidence: 95%
“…In line with this study, we showed that mCRP, but not pCRP, induces oBRB disruption, at least in vitro. Monomeric CRP disrupts the RPE barrier function by disturbing the expression and distribution of tight junctions and increasing paracellular permeability [77]. Likewise, mCRP upregulates the production of IL-8 and monocyte chemotactic protein-1 in RPE cells.…”
Section: C-reactive Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of other inflammation-driven pathological conditions that mCRP has recently been inextricably linked to. mCRP was shown to be present in drusen aggregates-the hallmark of age-related macular degeneration concomitant with an increased inflammatory activation of the retinal pigment epithelium and disruption of the outer blood-retinal barrier; mCRP was suggested to be involved in enhancing disruption and inflammation-associated progression of the disease (23). The plasma from a group of patients with sepsis, showed significantly higher levels of EVs bound to mCRP associated with enhanced IL-8 secretion compared with healthy individuals indicating a direct mechanism for perpetuation of the condition, whilst apheresis and removal of the mCRP was sufficient to reduce circulating cytokine levels (24); whilst, in autoimmune diseases such as lupus nephritis, highest levels of mCRP-antibodies in the serum was associated with worse symptomatic disease, increased expression of IL-6 and TNF-a, and clinical evidence of systemic lupus erythematosus (25).…”
Section: Evidence Of the Disease Modifying Behavior Of Mcrpmentioning
confidence: 99%
“…CRP has also been implicated in the breakdown of important biological barriers. For example, monomeric CRP can cross the retinal pigment endothelium and may cause macular degeneration through the disruption of the outer blood-retinal barrier [ 7 ]. Moreover, C-reactive protein (CRP) has been demonstrated to induce blood brain barrier (BBB) disruption in a process involving NAD(P)H-oxidase dependent oxidative stress [ 8 ].…”
Section: Introductionmentioning
confidence: 99%